(untitled) (E Global Congress, 2023)
This article analyzes various programs in the financial literacy and economic direction broadcast by international organizations, research by foreign economists on issues of improving financial literacy of the population through television programs, TV shows on the topic of financial literacy on foreign TV channels, information boards, TV shows. The article also explores the television projects of international organizations, the role and influence of television programs in the process of increasing the financial literacy rate of the population, and the requirements for it.